Electrodynamical Investigation of the Photonic Waveguide Structure - Gric, T.; Nickelson, L. (Elektronika ir Elektrotechnika, 2011)
Presented the electro dynamical analysis of the n-Si photonic waveguide structures. The rigorous solution of the problem was fulfilled by the Singular Integral Equations’ method (SIE) using the Muller’s method. Here the dispersion characteristics of six different structures with three, five and seven air holes are analyzed. The air holes are located symmetrically to the centre of the waveguide substrate in the first three structures. The air holes are shifted in the other examined structures. In the article dependencies of the phase constants and losses on the number of holes and their location with respect to the top and the bottom sides of the semiconductor substrate are presented. The dispersion characteristics’ comparison of waveguides with the different location of holes inside n-Si substrate shows that especially strong dependences are observed in the behaviour of losses. Ill. 5, bibl. 9 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.344